Synthesis and Magnetic Characteristics of N–Co Nanocomposites - Lisova, O.M.; Abramov, M.V.; Makhno, S.M.; Gorbyk, P.P. (Металлофизика и новейшие технологии, 2018)
The single-domain nanoparticles of NiCo, NiCo on the surface of graphene (NiCo@GNP) and NiCo on the surface of silica dioxide (NiCo@SiO₂) are synthesized. Their crystalline structure, surface morphology and magnetic characteristics of nanoparticle are investigated. It is shown that the magnetization curve of the nanoparticles ensembles in the form, which is distinctive for superparamagnets, and its calculations within the framework of the Langevin’s paramagnetism theory are satisfactorily consistent with the experimental results. The laws of particle size distribution in ensembles are established using the method of magnetic granulometry.